Quality Evaluation Of Geography Learning Program At SMA Negeri 1 Mayong Using Ekop Model - Wijayanto, Pradika Adi (JPI (Jurnal Pendidikan Indonesia), 2017)
The research purpose was to evaluate the quality of geography learning program in Public Senior High School 1 Mayong, Jepara Regency. The research was evaluative research with EKOP model, which is quality and learning output evaluation. Research sample was determined by purposive sampling technique. The collected data was from closed questionnaire answered by 37 students of XI IS 1 class and a geography teacher. The data was qualitative and had been described to conclude the research results. The results showed that teacherâ€™s performance value was 4,08 (good category); learning facilities value was 3,63 (good category); class atmosphere value was 3,28 (adequate category); studentâ€™s attitude value was 3,37 (adequate category); and the learning motivation value was 3,57 (good category). Learning output on academic and social proficiency was 4,49 (very good category). From the total recapitulation of learning quality, the value was 3,59. Therefore, it can be concluded that the quality of geography learning program was good.Â